Effect of Types and Depths of Media Filter to Reducing Turbidity Concentration - Fikry Ardianto; Euis Nurul H; Tuhu Agung; Aussie Amalia (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Rapid sand filter is used to decrease the turbidity consentration. This research purpose is find the comparation of variation media to reduced turbidity from Wonokromo River. Silica and zeolite are used to be the media of rapid sand filter with effective sizes of 0,20 mm and 1,40 mm. Variation that used in this research are rapid sand filter single media and dual media with depth of 60 and 80 cm in each variation. Rapid sand filter dual media uses silica and zeolite with the comparison of 50 : 50. The result showed that every variation has more than 50% removal of turbidity. Rapid sand filter single media with 60 cm of depth reach 84,35% of turbidity removal and with 80 cm of depth reach 92,22% of turbidity removal. Rapid sand filter dual media (silica and zeolite) with 60 cm of depth reach 73,48% and with 80 cm of depth reach 87,77%. Result showed that rapid sand filter single media with 80 cm of depth reach the highest removal in every variation. It’s concluded that the media depth and sizes effect the effictivity of turbidity removal.